Frequency of Spontaneous Bacterial Peritonitis in Asymptomatic Outpatients with Cirrhotic Ascites (Medical Forum Monthly, 2024)
Objective: The purpose of this Study is to ascertain the prevalence of spontaneous bacterial peritonitis (SBP) in asymptomatic cirrhosis patients who visit the Ayub Teaching Hospital's gastroenterology outpatient department.Study Design: A Cross sectional /Observational studyPlace and Duration of Study: This study was conducted at the Department of Gastroenterology Unit, Ayub Teaching Hopsital Abbottabad from 05 July 2022- 05 July 2023.Methods: A total of 157 asymptomatic cirrhotic patients with ascites who presented to the gastroenterology outpatient department were recruited for the study, and ascitic fluid analysis was performed to determine the presence of spontaneous bacterial peritonitis. The study was carried out using a non-probability consecutive sampling study design.Results: There were 157 patients in all, 96 of whom were female and 61 of them were male. On ascitic fluid analysis, spontaneous bacterial peritonitis is present in 33% (52/157) of asymptomatic cirrhotics with ascites, whereas 66% (105/157) do not.Conclusion: The results of our prospective investigation demonstrate that among asymptomatic cirrhotic patients with ascites in our setting, spontaneous bacterial peritonitis has a low prevalence.